2021
DOI: 10.1186/s12891-021-04341-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgeon-controlled variables on construct stiffness in lateral locked plating of distal femoral fractures

Abstract: Background Nonunion following treatment of supracondylar femur fractures with lateral locked plates (LLP) has been reported to be as high as 21 %. Implant related and surgeon-controlled variables have been postulated to contribute to nonunion by modulating fracture-fixation construct stiffness. The purpose of this study is to evaluate the effect of surgeon-controlled factors on stiffness when treating supracondylar femur fractures with LLPs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
(85 reference statements)
1
17
1
Order By: Relevance
“…The current study also evaluated varying working lengths of fixation, due to the custom nature of the locking plates utilized. Similar to previous mechanical studies, no significant effect of working length on construct stability was noted during compressive testing to failure [ 27 , 33 ]. However, one study noted differences in yield load, specifically, between constructs of short and long working lengths, and shorter working lengths were significantly associated with greater maximum load but not overall construct stiffness during cyclic compressive testing followed immediately by compressive load to failure [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study also evaluated varying working lengths of fixation, due to the custom nature of the locking plates utilized. Similar to previous mechanical studies, no significant effect of working length on construct stability was noted during compressive testing to failure [ 27 , 33 ]. However, one study noted differences in yield load, specifically, between constructs of short and long working lengths, and shorter working lengths were significantly associated with greater maximum load but not overall construct stiffness during cyclic compressive testing followed immediately by compressive load to failure [ 6 ].…”
Section: Discussionsupporting
confidence: 88%
“…Due to the retrospective nature of the study, we are unable to differentiate between the effects of overall plate length and the effects of fixation working length on fracture outcomes, and this represents a major limitation of the study. Previous in vitro and in vivo analyses of the effects of working length on locking plate fixation have yielded mixed results [ 6 , 10 , 12 , 33 ]. Using in vitro FEA modeling, Giordano et al described a direct correlation between increasing working length and construct stability through effective deflection of stress, but in mechanical testing of various working lengths for LCP fixation of canine femoral gap defects, Chao et al described significantly higher strength (yield load) in short compared to long working length constructs [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…longer) commercial DFLPs to find that stiffness increased linearly with WL/total plate length; but, stiffness versus total plate length data were not isolated. Also, Weaver et al 53 experimentally found 15% lower axial stiffness ( p = 0.003) for a 5-hole (i.e. shorter) versus a 13-hole (i.e.…”
Section: Resultsmentioning
confidence: 96%
“…Kandemir et al 20 experimentally showed 26% lower axial stiffness ( p = 0.003), 23% reduced axial failure strength (p value not reported), and 42% fewer axial cycles to failure ( p = 0.002) for a titanium versus steel commercial DFLP fixed to an artificial femur. However, Weaver et al 53 experimentally discovered no statistical difference in axial stiffness ( p = 0.12) for a titanium versus steel commercial DFLP implanted in artificial femurs, but they did not report if bone-on-bone contact occurred during fracture gap closure to explain this unexpected result. Similarly, Beingessner et al 60 experimentally measured no statistical difference in axial stiffness ( p = 0.51), but 34% lower torsional stiffness ( p < 0.001), for a titanium versus steel commercial DFLP mounted onto an artificial femur, while neither failed during axial cyclic loads reaching 1 kN.…”
Section: Resultsmentioning
confidence: 97%
“…The use of a longer plate construct is one of the factors a surgeon may choose for achieving union. 19 In this series, a careful selection of the length of the plate, screw–plate density, implant material (titanium plate was used) and appropriate reduction and compression at the site of non-union were made with the aim of avoiding failure. 20 , 21 The literature supports titanium as more of a biocompatible and flexible material with Young's modulus comparable to the bone as opposed to stainless steel.…”
Section: Discussionmentioning
confidence: 99%